+0  
 
0
107
1
avatar+2509 

Help.

NotSoSmart  Feb 5, 2018
 #1
avatar+87691 
+1

3)

 

y  =  -4x^2  - 2      add 2 to both sides

 

y + 2  =  - 4x^2     divide both sides by  -4

 

[ y + 2 ] / -4  =  x^2

 

[ - y - 2 ]  / 4   =  x^2      take both roots

 

±√ [ - y - 2 ] / 2    =  x        swap, x , y      

 

±√ [ -x - 2 ]  / 2   =  y          and this is the inverse

 

Here's the graph of both :

 

https://www.desmos.com/calculator/sdlfeedlri

 

 

cool cool cool

CPhill  Feb 5, 2018

20 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.